ОСОБЕННОСТИ ИММУННОГО ВОСПАЛЕНИЯ У БОЛЬНЫХ С ХРОНИЧЕСКОЙ ОБСТРУКТИВНОЙ БОЛЕЗНЬЮ ЛЕГКИХ И БРОНХИАЛЬНОЙ АСТМОЙ - А. Е. Шуганов; Ф. Н. Палеев; Н. А. Распопина; Ж. М. Салмаси; Е. Г. Шуганов (Архивъ внутренней медицины)
Background: To improve differential diagnosis of chronic obstructive pulmonary disease (COPD) and bronchial asthma (BA), identification of new biological markers is needed. Aim: To differentiate between COPD and BA using modern immunological methods. Results: Conducted a comparative study of surface markers of peripheral blood lymphocytes in peripheral blood lymphocytes, expresarse antigens CD3, CD4, CD8, CD16, CD20, CD23, CD25, CD54, CD71, CD72, HLA-DR, CD95 and membrane immunoglobulins mIgM and mIgG in patients with chronic obstructive pulmonary disease (COPD) and atopic asthma in the acute stage. Shows significant differences in the changes of surface phenotype of lymphocytes in the studied diseases. In addition, in COPD, there is a considerable increase in the content of cytotoxic lymphocytes (CD 4+, CD8+ and 34 %, CD16 + NK cells by more than 33 % of normal ) in the blood is not dependent on stage of the disease. It is suggested that the high cytotoxic potential of the immune system is the cause of more damage to the lung tissue, causing the development of pulmonaryfibrosis, emphysema and systemic damage in COPD. In patients with ABA during remission of the activity of cytotoxic cells is reduced, and observed the predominance of the processes of activation of apoptosis of lymphocytes (CD95) on their willingness to differentiation and acquisition of late differentiation antigen (HLA-DR). Received various changes in the immune response in patients with ABA and COPD allow a better understanding ofthe features of chronic inflammation in these diseases.